TINGKAT PENGETAHUAN IBU TENTANG SWAMEDIKASI DIARE ANAK DI PLUMBUNGAN DESA DUKUH KECAMATAN BANYUDONO KABUPATEN BOYOLALI - Ratih Dwi Purwanti; Dewi Weni Sari; Vania Santika Putri (Jurnal Farmasindo, 2023)
Diarrhea is a condition in which a person defecates mushy or liquid consistency, can be water only and the frequency is more (usually three or more) in a day. Improper handling and treatment of diarrhea can cause complications such as dehydration and malnutrition. This final project aims to measure the level of knowledge of mothers about diarrhea self-medication in children in Plumbungan, Dukuh Village, Boyolali Regency. This study is a quantitative descriptive research method with cross sectional data collection. The sampling total 42 samples were used for the sampling method. Retrieval of research data by filling out a questionnaire As a results the characteristics of respondents at the age of 26-35 years were mostly 45%. The most dominant last education was high school as much as 69%, and the most jobs were as housewives (IRT) as much as 43%. Mother's level of knowledge about diarrhea is categorized as good as much as 69%, sufficient category as much as 31%. The good level of self-medication behavior in children with diarrhea is 90%, 10% is sufficient. Overall, the average level of knowledge of mothers shows that mothers have good knowledge and behavior in dealing with children with diarrhea